Long-term trends of direct nitrous oxide emission from fuel combustion in South Asia. (1st April 2022) - Bansal, Sangeeta; Raghuram, Nandula; Adhya, Tapan Kumar; Rahman, Md Mizanur; Tshering, Dendup; Dahal, Khem Raj; Wakeel, Abdul; Aminath, Shazly; Safi, Zikrullah; Nissanka, Sarath; Pathak, Himanshu; Aziz, Tariq; et al.
Abstract: An increasing concentration of nitrous oxide (N2 O) in the global atmosphere can perturb the ecological balance, affecting the climate and human life. South Asia, one of the world's most populous regions, is a hotspot for N2 O emission. Although agriculture traditionally dominated the region, economic activities are rapidly shifting towards industry and energy services. These activites may become the largest emitters of N2 O in future. Yet, few attempts have been made to estimate long-term direct N2 O emission from fuel combustion for the different energy-consuming sectors in the South Asian region. Therefore, the present study developed a comprehensive sectoral N2 O emission inventory for South Asian countries for the time period of 1990–2017, with projections till 2041. It revealed that the average N2 O emission from fuel combustion in the South Asia region is about 40.96 Gg yr −1 with a possible uncertainty of ±12 Gg yr −1, showing an increase of more than 100% from 1990 to 2017. Although India is the major contributor, with an average of 34 Gg yr −1 of N2 O emissions, in terms of growth, small countries like Bhutan and Maldives are dominating other South Asian countries. Sector-wise, the residential sector contributed a maximum emission of 14.52 Gg yr −1 of N2 O but this is projected to reduce by more than 50% by 2041. This is because of the successful promotion of cleaner fuels like liquefied petroleum gas over more polluting fuelwood. Power generation contributed 9.43 Gg yr −1 of N2 O emissions, exhibiting a maximum growth of 395%, followed by road transport (289%) and industry (231%). Future N2 O emissions from transport, power and industry are projected to rise by 2.8, 3.3, and 23.9 times their 2017 estimates, respectively, due to the incapability of current policies to combat rising fossil fuel consumption. Mitigation options, such as replacing diesel and compressed natural gas vehicles with electricity-driven vehicles, can decelerate N2 O emissions to 45% by 2041 for road transport. A 41% reduction is possible by displacing coal with renewables in the power and industry sectors. Overall, the South Asian contribution to global N2 O emissions has enlarged from 2.7% in 1990 to 5.7% in 2007–2016, meaning there is an urgent need for N2 O emission mitigation in the region.